The cross‐section of routine practice of echocardiographic diastolic evaluation in atrial fibrillation in a community hospital: A quality improvement project. Issue 12 (14th November 2022) - Yang, Ji Hyun; Dani, Sourbha S.; Kim, Seong Yoon; Kinzfogl, George; Davidson, Eric
Abstract: Background: The echocardiographic assessment of diastolic function in the context of atrial fibrillation (AF) has been controversial and can be challenging and labor‐intensive. We aimed to assess the actual practice of diastolic evaluation in AF in our community hospital echocardiography laboratory and to improve clinical performance by a quality improvement project. Methods: We reviewed 244 echocardiograms in patients with AF at the time of echocardiography from November 2019 to November 2020 (pre‐intervention phase). We classified cases into a complete versus incomplete evaluation group according to the completeness of diastolic parameter measurement. After an educational intervention, we reviewed 68 echocardiograms in patients with AF from August 2021 to October 2021 (post‐intervention phase). Results: Our results demonstrated an improvement in a complete diastolic assessment from 69% to 91% after intervention ( p < .001). In the pre‐intervention phase, the four parameters (mitral inflow pulsed wave Doppler image, left atrium volume index, mitral annular tissue Doppler image [TDI], and tricuspid regurgitation Vmax), mitral annular TDI was not acquired in 71 out of 244 cases (29.1%) and those cases were classified as incomplete evaluation group. Interestingly, in the pre‐intervention phase, 57 out of 162 cases (35%) with preserved EF (≥50%) received significantly more incomplete diastolic evaluation than 14 out of 82 patients (17%) with reduced EF (<50%) ( p = .004). There were no statistically significant differences in age, BMI, the reason for requesting echocardiography, and patient level of care between the complete and incomplete evaluation groups. In the post‐intervention phase, completeness of diastolic measurement in AF was significantly improved compared to the pre‐intervention phase (29% vs. 9%, p < .001, respectively). Conclusion: A quality improvement project effectively improved the clinical performance of diastolic evaluation in AF in our community echocardiography laboratory. After the intervention, we decreased an incomplete evaluation from 30% to 9%. More efforts should be needed to increase awareness and familiarity in evaluating diastolic function in AF.